Analysis of Competitiveness and Factors Affecting Indonesian Clove Exports in Five Main Destination Countries - Ridhatama, Hafidz; Iranto, Dicky; Wiralaga, Harya Kuncara (Journal of Business and Economics Research (JBE), 2024)
This study aims to analyze the competitiveness and factors affecting Indonesian clove exports in five main destination countries. Competitiveness analysis using the Revealed Comparative Advantage (RCA) method. Analysis of factors affecting Indonesian clove exports using gravity models and panel data regression methods processed using E-Views 12 software. This study uses secondary data with five research objects, namely Malaysia, UAE, Singapore, Saudi Arabia, and Vietnam, from 2012-2021, sourced from BPS, Ministry of Trade, UN Comtrade, International Trade Center (ITC), World Bank, and FAO. The results of RCA analysis show that Indonesian cloves are worth an average of above one, which means they have a strong comparative advantage and competitiveness in the five main destination countries. The results of factors affecting Indonesia's clove exports found that the real GDP of destination countries had a positive effect with a regression coefficient value of 12.27291 and was significant at the level of 5% with a probability of 0.0036 on the volume of clove exports. Export prices have a positive effect with a regression coefficient value of 0.871995 and are significant at the level of 5% with a probability of 0.0138 on the export volume of cloves. Meanwhile, economic distance has a negative effect with a regression coefficient value of -13.26768 and is significant at the level of 5% with a probability of 0.0144 on the export volume of cloves. The implications of this study show that Indonesian cloves have a comparative advantage and strong competitiveness, so clove farmers must be able to take advantage of the market conditions of destination countries and map countries with a large demand for cloves. Farmers can pay attention and take advantage of clove export prices in the international market, as well as consider the distance to the destination country which can affect transportation costs. In addition, the Indonesian government must be able to take into account the economies of clove importing countries to determine the implementation of clove export strategies.